MEDIASI TERHADAP PENYELESAIAN SENGKETA HAK MILIK ATAS TANAH DI WILAYAH HUKUM PENGADILAN NEGERI BENGKALIS - Irham, Muhammad; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The dispute settlement through mediation prioritizes the principles of deliberation to achieve consensus that is in harmony with the culture of the Indonesian nation, then it is proper that the mediation is applied maximally in every process of dispute settlement in court. Integrated mediation in the courts is a process of dispute settlement that must be taken as an instrument to reduce the burden of civil litigation in court, the active role of the parties in mediation with the help of a neutral mediator judge to achieve the peace process through simple mediation, fast and low cost. This study aims to gain clarity about the process of mediation in court which includes the stages of mediation and the effectiveness of the mediation in case reduction, the constraints faced by the courts and efforts to overcome them.The problems in this research are 1) How is the procedure of mediation to settlement of land ownership dispute in the District Court of Justice of Bengkalis based on Supreme Court Regulation Number 1 Year 2008 About Mediation Procedure in Court? 2) How is the effectiveness of the implementation of mediation in the settlement of land ownership disputes in the Legal District of Bengkalis District Court? 3) What are some barriers that occur in mediating the settlement of land ownership disputes in the Legal District of Bengkalis District Court? This research method uses Juridical Empirical approach. The location of this research was conducted in the jurisdiction of Bengkalis District Court. The population in this research is the Chairman of Bengkalis District Court, Bengkalis District Court Judge, Mediator. The data source of this research is primary data and secondary data by collecting data through interview, literature study. The data analysis technique used is qualitative.The general picture in this study is a description of the mediation concept in the Court, a picture of the mediation and a description of the settlement of land rights disputes. The description of the mediation concept in the court discusses the scope, objectives, principles, and mediation process, the Overview of mediation discussing the roles, functions, and tasks of mediators. A description of the settlement of land disputes addresses the settlement of land disputes through the Court and outside the Court.The process of conducting mediation in the courts includes stages of a general and non-detailed regulation commencing with the registration of a lawsuit by the party by paying court fees and determining the judge and summoning the parties, in the pre-mediation phase of the panel of judges explaining the mediation and proceeding with the judges' the mediation process of submitting a resume and receiving a peace option from a mediator judge and proceeding with a meeting or caucus session, the final stages of mediation result in a peace agreement or failure. The cause of the failure of mediation due to the limitations of mediators, facilities, and lack of support from the parties, the efforts undertaken in order to carry out mediation proceed effectively with the criteria of mediator judgment and the provision of space for mediation and peace options offered to the partiesKeywords: Mediation Engineering - Settlement - Land Rights – Mediator